Plan de negocios para la producción y comercialización de bolsas biodegradables a base de almidón de yuca en la ciudad de Quito - Sigcha Pilatuña, Andrea Alejandra (2020)
This business plan wants to create a company for the production and trade of biodegradable bags in the city of Quito. This idea was born in order to create a new and innovative product that will reduce the environmental impact that our planet suffers due to inadequate use of plastic. Plastic takes more than 100 years to fully disintegrate, which affects the lives of marine animals and entire ecosystems. Which is why an analysis of the external surroundings of the industry was carried out through a study of pestel and porter, this was done with the purpose of identifying opportunities and threats found in said industry. Likewise, a complete investigation of the client was carried out with the use of key tools in quantitative and qualitative research to determine consumer profile, tastes and preferences that directly influence the purchase decision. In addition, to position the product in the market, a marketing plan was created and linked to a product differentiation strategy which considers the 4p's and is focused on the needs and desires of the market segment. Finally, a financial plan was carried out with a five-year projection to determine the degree of economic and financial viability that the company can incur with this type of business model; it considers specific indicators that help in decision making. It should be noted that by using valuation criteria and comparing it with the discount rate, it demonstrated that the proposed project is profitable.